Drivers of Corporate Social Performance: Evidence from Malaysia Domestic Banks - Chai, Guo Le; Lee, Ai Sean; Lee, Hui Shuang; Yeoh, Xue Jing (2017)
This study aims to examine the effect of corporate financial performance against the corporate social performance of domestic banks in Malaysia. The independent variables including in this study are corporate financial performance, bank size, leverage level and bank age to investigate its consequences on dependent variable, which is corporate social performance of domestic banks in Malaysia. This study is using panel data, consists of time series data from 2007 to 2015, and cross-sectional data with 10 domestic banks, which contains 90 observations. Moreover, this study employed Panel Data Regression Model to examine the regression model. For the diagnostic checking, the model is free from the econometric problems except heteroscedasticity issue, which had been solved by using Cluster Robust Standard Error. The results indicate the corporate financial performance and bank age are significantly and positively related except for bank size and leverage level are insignificantly and negatively related to corporate social performance of domestic banks in Malaysia.